Naturalistic Dispersion of the Problem of Social Cognition - Karosas, Justinas (Problemos, 1998)
Having grown together, pure practicality and rationality were perhaps the most essential external feature of the newly established industry of the 18th-19th centuries. Therefore, having employed external powers, the philosophy of this period made efforts to limit itself from speculations and become the positive science which would be related to the natural sciences. Although it recognises that the social cognition is engaged, it contemplates that a social theory can avoid this engagement to a certain extent by finding a neutral code with respect to values in the social life. This code is the character of naturalness of each individual, which as a composite part lies in the whole body of the society. This particular code has to undergo research according to the philosophers of the New Age and positive social science.